Forms of Affixation Morphological Errors in Speech Texts of Grade VIII Students SMP Swasta Cerdas Bangsa - Ginting, Angelina Pascalia; Simanjuntak, Dairi Sapta Rindu; Gultom, Candra Ronitua; Sihite, Jernyta (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the forms of affixation morphological errors in speech texts written by eighth-grade students of the Smart Bangsa Private Junior High School. This study uses a qualitative descriptive method. The study was conducted at the Smart Bangsa Private Junior High School in the 2024/2025 academic year. The study population was 80 eighth-grade students' speech texts. The sample consisted of 75 texts selected purposively. Data collection on the forms of affixation morphological errors in speech texts was carried out through documentation techniques based on observation guide sheets. The observation guidelines were compiled using objective and systematic steps. Data analysis of the forms of affixation morphological errors in speech texts used the distribution method supplemented by advanced techniques, including the lesap technique and the ganti technique. The results of the study, based on the analysis of 75 data points, showed that only 23 data points contained affixation errors. The types of errors that appeared included errors in the use of prefixes, errors in the use of suffixes, and errors in the use of confixes. The most dominant error was in the use of prefixes. Meanwhile, errors in the use of infixes were not found. This finding shows that students still experience difficulties in applying the rules of affixation morphology correctly, especially in formal writing contexts such as speech texts.